Avaliação de comportamentos relacionados a ansiedade, autoadministração de etanol e expressão de pró-dinorfina e Fos em regiões encefálicas de animais adultos expostos à nicotina durante a adolescência - Bianchi, Paula Cristina (2014)
Adolescence marks a period of increased vulnerability to drug abuse. Early initiation of tobacco use is strictly associated with alcohol use and dependence in adolescence and adulthood. The present study aims to investigate: 1) changes in anxiogenic-like effects and on operant ethanol self-administration in adult rats exposed to nicotine during adolescence; 2) changes on pro-dynorphin (PDYN) gene expression in the nucleus accumbens (NAc) on late nicotine withdrawal and after ethanol self-administration; 3) which brain areas are activated on short or long-term nicotine withdrawal during adolescence. Our results showed that pre-exposure to nicotine during ten days (3mg/kg/day; s.c) in adolescent rats, did not change anxiogenic-like effects in the elevated plus maze, 15 days after the treatment cessation [postnatal day (PND) 52], progressive ratio (PND 75-79) and binge (PND 81-84) in the operant ethanol selfadministration protocol. However, animals pre-treated with nicotine displayed increased motivation to saccharin seeking. No changes were observed on gene expression of PDYN 15 days after chronic nicotine treatment cessation or 24 hours after the last binge session of ethanol self-administration. Concerning the areas involved on nicotine withdrawal, we observed that adolescent rats exposed to nicotine through the minipumps during 10 days (PND 28-37), showed enhanced Fos activation in the medial prefrontal cortex (mPFC) 3 days after nicotine treatment cessation (PND 40). The percentage of neuronal activation in this group was 22.03%, of those activated neurons, 28.5% were GABAergic and only 2.5% were glutamatergic neurons. Meanwhile, 15 days after the mini-pumps were removed, no difference was observed on Fos activation in the different brain areas analyzed. We concluded that: a) administration of nicotine during adolescence was not able to modify anxiety-like behaviors and ethanol seeking behavior in adulthood; b) late nicotine withdrawal did not change gene expression of PDYN in NAc, as well as, did not change Fos protein neuronal activation in the regions of mPFC, NAc and habenula; c) short-term nicotine withdrawal involves the activation of neural ensembles in the mPFC.